Analysis of Science Literacy Skills of Students in X Class at High Schools in Yogyakarta City on the Competency Aspect in Biology Learning - S, Riska Herlena; Aloysius, Suyitno (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the level of science literacy skills of students in X class at high schools in Yogyakarta City in the subject of biology based on PISA science literacy indicators. This research is a quantitative descriptive study using the survey method. The data collection technique used tests in the form of questions based on science literacy indicators in the competency aspect. The data analysis technique is inferential statistics with non-parametric statistics using the Kruskal-Wallis test to determine whether there are significant differences in each school. The research results show that the science literacy skills of public high school students in Yogyakarta City are in the low category with an average score of 57,88%. Further tests indicate significant differences among each school.